2021
DOI: 10.1038/s41598-021-03447-w
|View full text |Cite
|
Sign up to set email alerts
|

Materials degradation in non-thermal plasma generators by corona discharge

Abstract: Atmospheric corona discharge devices are being studied as innovative systems for cooling, sterilization, and propulsion, in several industrial fields, from robotics to medical devices, from drones to space applications. However, their industrial scale implementation still requires additional understanding of several complex phenomena, such as corrosion, degradation, and fatigue behaviour, which may affect final system performance. This study focuses on the corrosive behaviour of wires that perform as a high-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In addition, it is need to point out that tungsten wire rather than stainless steel wire was chosen in the investigation due to its higher strength and durability. It was reported that the stainless steel wire is easy to break during the long term operation due to the erosion induced by discharge [38]. Actually the filtration efficiency of EES with stainless steel multi-wire array electrode was also measured(data was not shown) and its filtration efficiency of PM 0.3 ∼ 0.5 and PM 0.3 were still significantly higher than the other two discharge electrode structure at the same voltage.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it is need to point out that tungsten wire rather than stainless steel wire was chosen in the investigation due to its higher strength and durability. It was reported that the stainless steel wire is easy to break during the long term operation due to the erosion induced by discharge [38]. Actually the filtration efficiency of EES with stainless steel multi-wire array electrode was also measured(data was not shown) and its filtration efficiency of PM 0.3 ∼ 0.5 and PM 0.3 were still significantly higher than the other two discharge electrode structure at the same voltage.…”
Section: Discussionmentioning
confidence: 93%
“…The main disadvantages of using the corona discharge method are corrosion, degradation, and fatigue behavior of the electrode, which can affect the performance of the processes negatively. Cádiz et al [ 70 ] studied the degradation of corona electrodes. They showed that the surface of the electrode is destroyed after a short time of use regardless of the material from which it is made.…”
Section: Types Of Plasma Reactorsmentioning
confidence: 99%
“…The corona phenomenon is a nonthermal plasma generation system that is distinguished from others by being easily achievable and controllable through the modification of design and performance parameters. [2][3][4][5] Many research studies have been conducted on developing electrode configurations for industrial applications, including wire-to-plane, wire-to-cylinder, point-to-grid, and blade-to-plane fins. [5][6][7][8][9] The high energy produced is transformed on the one hand into kinetic energy, causing the ionic wind, and on the other hand into chemical energy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main advantages of this technology is that it can be easily produced from air and electricity, providing a lower‐cost disinfection solution without the expense and logistics of maintaining it. The maintenance of the EHD devices could be estimated based on the results obtained by Cogollo de Cádiz et al [ 4 ] who studied the behavior of different materials for the corona.…”
Section: Introductionmentioning
confidence: 99%